Restructuring the world economy - Kolko, Joyce (Pantheon Books, 1988)
Focuses on the restructuring that must take place in national economieswhether free market or centrally controlled; Analyzes how capital, labor, and government relate to the crisis and also takes a critical look at world trade, monetary relationships, and the role of international agencies